IMPLIKASI EPISTEMOLOGIS PEMIKIRAN FILSAFAT PAUL KARL FEYERABEND: KEBEBASAN AKADEMIK DALAM PENGEMBANGAN ILMU PENGETAHUAN ISLAM - M. Agus Wahyudi; Syamsul Rijal; Silahuddin Silahuddin; M Ikhwan (Academic Journal of Islamic Principles and Philosophy, 2023)
Paul Karl Feyerabend has an idea called Epistemological Anarchism, which is a method used to criticize the establishment of knowledge with the aim of developing science itself. Academic freedom is one of the attitudes to develop knowledge while prioritizing objectivity. This research will discuss the implications of Feyerabend's thinking on developing knowledge and science in Islam. This research uses a library research approach with the method of collecting library data related to the research topic. The study results show that Feyerabend's concept of epistemological anarchism holds that there are no methodological rules in the development of knowledge and science. Feyerabend, finding a truth does not have to be through unnecessary falsification, but a truth can be found through new theories that have practical benefits. Epistemological anarchism has relevance to the epistemology of science development in Islam, namely as a way or steps to obtain educational knowledge based on Islamic fundamentals.